Levantamento epidemiológico de lesões orais potencialmente malignas em um centro de referência na Bahia - Leal, Katherine Lordêlo (2013)
It is mandatory to recognize its previous wounds of mouth cancer, the alleged "potentially malignant injuries" - leukoplakia, cheilitis, erythroplakia and oral lichen planus - with the objective of avoiding its development. A transversal cut study was performed in order to estimate the prevalence of potentially malignant lesions diagnosed at the Centro de Referência de Lesões Bucais of Universidade Estadual de Feira de Santana and as a means to register the accompaniment of the patients through potential clinical outputs of these lesions informed on the patient's reports from 1996 to 2012. A descriptive analysis of all variables was carried out, followed by the X2 Test of Pearson, which was used as a way of calculating the statistic significance. As a measure of association between the mouth lesion and the studied patient's likely risk factors, the Prevalence Reason calculation was performed within a population interval of 1 standard deviation. Leukoplakia was the most prevalent injury (43,6%) and erythroplakia the least one (13,7%). A statistic significance was observed among all associations of injuries with the variables related to the patient (p<0,05), as well as the lesions and the consummation of its probable risk factors (p=0,00). In the Prevalence Reason calculation, significant results were observed, among which: the leukoplakia and the exposition solely to alcohol (RP=2,47; IP=1,72-3,55); the erythroplakia and the exposition solely to alcohol (RP=2,51; IP=1,38-4,55) and to alcohol and tobacco (RP=1,8; IP=1,23-2,64); the actinic cheilitis and the exposition to solar radiation (RP=2; IP=1,61-2,50) and the solely to tobacco (RP=2,51; IP=1,75-3,59); and the oral lichen planus and the exposition solely to tobacco (RP=2,46; IP=1,80-3,36) and to alcohol and tobacco (RP=3,04; IP=2,11-4,35). Out of the total number of patients, 4,6% of them presented a new wound, among which 52,6% of them were recurrent, half presented by oral lichen planus. Concerning the clinical output, 58,3% of all cases accompanied presented an injury permanence state and 26,9% were in the process of evolving to healing, no case of evolution to mouth cancer was detected. It is mandatory to stimulate the production of studies in such field for they will support protection, prevention, control, and the treatment of the mouth lesions here explored.